Методичні засади оцінювання соціальної безпеки держави - Дзьоба, О.Г.; Ставнича, Н.І. (Економіка природокористування і сталий розвиток, 2020)
Проаналізовано науково-методичні підходи до оцінювання рівня соціальної безпеки держави, узагальнено методи його здійснення. Акцентовано на виборі показників різних методик. З’ясовано, що найчастіше для такої оцінки використовується інтегральний показник.
Наведено авторське трактування поняття соціальної безпеки та її чотири складові – життя, бідність, здоров’я, освіта. Визначено набір показників для кожної із них. Запропоновано ієрархічну модель оцінювання соціальної безпеки та алгоритм розрахунку інтегрального показника. Summary the article has analyzed the existing scientific and methodological approaches to assessing the level of social security of the state. It was revealed that they differ because: scientists include various components that form social security; they use various indicators and calculation methods; have various aspects of both generalization and practical direction.
It was revealed that most often the components of social security include: safety of life, health, social protection and aspects of social and labor relations. The methods that are most often used in calculating the level of social security were considered. It was proved that in assessment, the selection of indicators that pose a threat, is the difficult task. It was revealed that there is no legally approved methodology for assessing the social security of the state. The use of various social security assessment methodologies was analyzed. Emphasis was placed on the selection of indicators used in these techniques. It was concluded that for assessing the social security of the state, an integral indicator is used most often. At the same time, scientists prefer their own set of indicators.
The author’s definition of «social security» was presented, which allowed the formation of four components of the state’s social security (life, poverty, health and education). It was established that the choice of indicators for assessing the social security of the state should cover a retrospective period and should be based on both reporting and calculated data. A hierarchical model of an integral indicator of state social security was proposed. There was defined a set of indicators for each of proposed component. The following algorithm has been proposed for assessing the integral indicator of state social security: the formation of the components of social security and the definition of indicative indicators for each of the components; formation of a database; determination of an integral indicator; determining the influence of each component on the change in the integral indicator; interpretation of indicators; determining the sustainability of hazardous trends.